2023
DOI: 10.1088/1674-1056/acac11
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical analyses of electrohydrodynamic force according to air pressure

Abstract: Electrohydrodynamic (EHD) force induced by corona discharge has been suggested as a new thrust for solar planes and stratosphere balloons in near space. However, its performance at low air pressures remains to be clarified. An experiment to measure the EHD force at pressures of 0.02~1.0 atm has been carried out with the wire-to-cylinder geometry. The drift-diffusion model with two-dimensional numerical simulation is used to analyze the ions’ distribution. The experiment result shows that the EHD force is not l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…They found that at air pressures lower than 1 atm, the wind speed remained relatively constant, but the energy consumption of negative coronas increased as the pressure decreased. Quan et al [34] used a wire-cylinder electrode to generate ion wind and studied the effects of air pressure and other factors on the thrust. Their research found that under low air pressure, increasing corona current did not lead to proportional growth in thrust.…”
Section: Introductionmentioning
confidence: 99%
“…They found that at air pressures lower than 1 atm, the wind speed remained relatively constant, but the energy consumption of negative coronas increased as the pressure decreased. Quan et al [34] used a wire-cylinder electrode to generate ion wind and studied the effects of air pressure and other factors on the thrust. Their research found that under low air pressure, increasing corona current did not lead to proportional growth in thrust.…”
Section: Introductionmentioning
confidence: 99%